Harrison's endocrinology - Jameson, J. Larry; Harrison, Tinsley Randolph 1900-1978 (McGraw-Hill Medical, 2013)
Featuring a compilation of chapters on endocrinology that appear in Harrison's Principles of Internal Medicine, Eighteenth Edition, this concise, full-color clinical companion delivers the latest knowledge in the field backed by the scientific rigor and authority that have defined Harrison's. You will find content from renowned editors and contributors in a carry-anywhere presentation that is ideal for the classroom, clinic, ward, or exam/certification preparation. Features: An organization that reflects the physiologic roots of endocrinology: Pituitary, Thyroid, and Adrenal Disorders; Reproductive Endocrinology; Diabetes Mellitus, Obesity, Lipoprotein Metabolism; Disorders Affecting Multiple Endocrine Systems; and Disorders of Bone and Calcium Metabolism. An important introduction that uses numerous examples of translational research to link genetics, cell biology, and physiology with pathophysiology and treatment Integration of pathophysiology with clinical management. 108 high-yield questions and answers drawn from Harrison's Principles of Internal Medicine Self-Assessment and Board Review, 18 edition. Updates and new developments since the publication of Harrison's Principles of Internal Medicine, 18 edition, 29 chapters written by physicians who are recognized experts in the field of endocrinology. Helpful appendix of laboratory values of clinical importance.